A biologically-inspired multi-joint soft exosuit that can reduce the energy cost of loaded walking. Issue 1 (December 2016) - Panizzolo, Fausto; Galiana, Ignacio; Asbeck, Alan; Siviy, Christopher; Schmidt, Kai; Holt, Kenneth; Walsh, Conor
Abstract Background Carrying load alters normal walking, imposes additional stress to the musculoskeletal system, and results in an increase in energy consumption and a consequent earlier onset of fatigue. This phenomenon is largely due to increased work requirements in lower extremity joints, in turn requiring higher muscle activation. The aim of this work was to assess the biomechanical and physiological effects of a multi-joint soft exosuit that applies assistive torques to the biological hip and ankle joints during loaded walking. Methods The exosuit was evaluated under three conditions: powered (EXO_ON ), unpowered (EXO_OFF) and unpowered removing the equivalent mass of the device (EXO_OFF_EMR ). Seven participants walked on an instrumented split-belt treadmill and carried a load equivalent to 30 % their body mass. We assessed their metabolic cost of walking, kinetics, kinematics, and lower limb muscle activation using a portable gas analysis system, motion capture system, and surface electromyography. Results Our results showed that the exosuit could deliver controlled forces to a wearer. Net metabolic power in theEXO_ON condition (7.5 ± 0.6 W kg−1 ) was 7.3 ± 5.0 % and 14.2 ± 6.1 % lower than in theEXO_OFF_EMR condition (7.9 ± 0.8 W kg−1 ;p  = 0.027) and in theEXO_OFF condition (8.5 ± 0.9 W kg−1 ;p  = 0.005), respectively. The exosuit also reduced the total joint positive biological work (sum of hip, knee and ankle) when comparing theEXO_ON condition (1.06 ± 0.16 J kg−1 ) with respect to theEXO_OFF condition (1.28 ± 0.26 J kg−1 ;p  = 0.020) and to theEXO_OFF_EMR condition (1.22 ± 0.21 J kg−1 ;p  = 0.007). Conclusions The results of the present work demonstrate for the first time that a soft wearable robot can improve walking economy. These findings pave the way for future assistive devices that may enhance or restore gait in other applications.